Chinese exploration of Orthodox theology a critical review - Lai, Pan-Chiu (2018)
In spite of the small number of Orthodox Christians in China, Chinese publications relating to Orthodox Christianity, in which many Chinese theologians from other Christian denominations or scholars without formal religious affiliation have been involved in exploring Orthodox theology, have mushroomed in recent years. It is noticeable that these explorations have been shaped not only by the renaissance of Orthodox theology in the twentieth century, but also by the Chinese context. In terms of scope, many of them are related to the Chinese context, including the relationship between Christianity and Chinese culture. In terms of depth, due to the religious backgrounds of the researchers, some of these Chinese explorations fail to integrate the theological, liturgical and spiritual dimensions of the Orthodox tradition, and exhibit difficulties in interpreting, for instance, Orthodox mystical theology. These limitations can be overcome through dialogue with contemporary Orthodox theologians.
Keywords: Chinese culture; Confucianism; Orthodox Theology; Sino-Christian theology; Deification; mystical theology; Theosis